'We are not poor things': territorio cuerpo-tierra and Colombian women's organised struggles. (August 2021) - Rodriguez Castro, Laura
In this article, I use Lorena Cabnal's notion of territorio cuerpo-tierra to analyse seventeen in-depth interviews with women leaders of rural social movements and other organisations in Colombia . In the interviews, social leaders condemn violence that is epistemic, systemic, militarised and that permeates all ambits of life. They denounce how the coloniality of power operates, while at the same time they propose alternatives for a better life from their own cosmovisions by enacting food sovereignty and constructing feminisms from 'below'. I demonstrate how these social leaders' actions are entangled in decolonial feminist struggles, which undermine the way in which women in the Global South have been constructed as 'objects' or 'in need of saving'. These women are not 'victims who need saving', but politically active subjects who enact change locally and nationally through their 'territories bodies-lands'. Not only do their narratives highlight the intimate relationship of the body with the land, but I argue that we must follow their lead in order to dismantle the coloniality of power.